Karzinomverdächtiges Magenulkus Teil 2 - Vieth, Michael; Langner, Cord (Pathologe, 2012)
Differentiation between pseudoneoplastic regenerative epithelium and gastric carcinoma can be challenging. In cases with pseudoneoplastic regeneration, so-called lateral expansion of tubules and changing of nuclear rows within one gland should not be present. The gastritis status is of particular significance as gastric cancer is a rare occurrence without Helicobacter pylori infections.
CRIS-Team Scopus Importer:2025-03-05